Impact of Human Umbilical Cord Blood Mononuclear Cells on Gentamicin-Induced Renal Injury and Genotoxicity in Rats - Ali H. Abu Almaaty; Reham A. Elmasry; Mayada S. Farrag; Fayez Althobaiti; Adil Aldhahrani; Eman Fayad; Mona A. Hussain (Frontiers in Medicine, 2021)
Background: Acute kidney injury (AKI), also known as acute renal failure (ARF), has received considerable critical attention in recent years. Gentamicin (GM) is an antibiotic whose prolonged use results in AKI with a high mortality rate.Methods: Fifty adult female albino rats weighing 150–200 g were used. The animals were divided into five groups: the first group was the normal healthy control one, the second group received only 1 × 106 HUCB mononuclear cells (MNCs)/rat by intravenous (iv) injection, the third diseased group was given GM 100 mg/kg for 10 consecutive days by intraperitoneal injections, the fourth preventive group received 1 × 106 HUCB MNCs/rat by iv injection 24 h before gentamicin treatment, and the fifth treated group received 1 × 106 HUCB MNCs/rat by iv injection 24 h after gentamicin treatment. After 1 week of treatment, blood samples were collected, and kidneys were removed for histopathological examination.Results: Rats treated with HUCB MNCs in the treated group had a significant decrease in renal damage, low levels of biomarkers for nephrotoxicities such as serum creatinine and blood urea nitrogen, and low chromosomal aberrations compared to the diseased third group. The gene expression of KIM-1 and NGAL was decreased in response to HUCB treatment.Conclusions: HUCB MNCs have a curative effect against AKI and gentamicin-induced genotoxicity owing to their regenerative property.